The Influence of Understanding Fiqh Subjects on the Prayer Discipline of Grade IX MTs Students - Alya Anjani; Syarifah Gustiawati Mukri; Nurman Hakim (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the influence of students’ understanding of Fiqh on their discipline in performing prayers among ninth-grade students at MTs Al-Ahsan. This study employs a quantitative approach using a correlational method. The study population consists of all 318 ninth-grade students at MTs Al-Ahsan, with a sample of 175 students selected through simple random sampling. Data collection was conducted through observation, questionnaires, and documentation. The research instruments used a Likert scale that had undergone validity and reliability testing. Data analysis was performed using descriptive statistics, normality tests, linearity tests, Pearson Product Moment correlation tests, simple linear regression, and the coefficient of determination. The research results indicate that students’ level of understanding of Fiqh falls into the moderate category with an average score of 59.24; similarly, their level of prayer discipline is also classified as moderate with an average score of 51.09. Hypothesis testing results reveal a positive and significant relationship between students’ understanding of the Fiqh subject and their prayer discipline in the 9th grade at MTs Al-Ahsan. This indicates that the better students’ understanding of Fiqh material, particularly regarding prayer, the higher their discipline in performing prayers. Based on these results, it can be concluded that an understanding of Fiqh plays a significant role in fostering students’ discipline in prayer.